PENGARUH SISTEM SELF-ASSESSMENT DAN TAX AMNESTY TERHADAP KEPATUHAN WAJIB PAJAK DI POS PEMERIKSAAN PRATAMA JAKARTA TEBET - Nizmah Nizmah; Bambang Iman Santoso; Maryam Maryam; Saud Sihombing; Jihan Jihan; Suhardi Kamaluddin (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
The purpose of this study was to determine the impact of a system of self-assessment and tax amnesty to the compliance against the requirements of the taxpayer in the Tax Inspectorate Tebet Jakarta. Multiple regression analysis was used in this study. All taxpayers who are registered in the Tax Administration of Tibet included in this study. The formula of this research is to use a measurement scale on the Likert scale.. And the total number of people in this sample is 100 (one hundred). The results of this study show that the system self-assessment and tax amnesty influence taxpayer compliance against the Requirements of the Tax Inspectorate Tebet Jakarta. This is indicated by the results of Fcount in 93.986 and Ftable 3.090, which shows that the Fcount is greater than Ftable, and that its own assessment on the quality of the systemic and the variables of the Tax Amnesty has a significant impact on compliance with the requirements of the taxpayer in the Tax Inspectorate Tebet Jakarta.